Cultural dimensions : factor analysis of Textor's 'A cross cultural summary' : a dissertation presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Education at Massey University - Stewart, Robert A. C. (Massey University, 1970)
Textor's A Cross-Cultural Summary is a computer produced compilation of significant relationships between all the extant cross-cultural variables that were available in 1966. Together with two coefficients of association (phi and chi square), and levels of significance, the relationships are also expressed in verbal form. In order, however, to reduce these findings to more manageable proportions and to obtain basic underlying factor dimensions which account for the relationships between the variables, a principal components analysis and Varimax rotation was conducted. The first 488 variables from the Summary were used. Also included was a review of cross-cultural research to date, and the problem of sampling as related to the area. A random stratified sample of 98 cultures was drawn from Textor's (1967) list of cultures for which there were at least 6 samples of contributions (not including contributions of the ethnographic Atlas). Specific hypotheses of "Bibliographic Selection Bias" relating to this sample were tested, using actual comparisons in the Summary. Twelve factors of phi were obtained, and a thirteenth factor was disregarded as it accounted for less than 5% of the total variance. The factors were rotated to the Varimax criterion to approach Thurstone's simple structure. Factor scores were computed for each culture on each factor dimension. For each of the following factors, the cultures with the highest positive and negative factor scores are given in order: Factor One: Structural Complexity (Thai, Copper Eskimo); Factor Two: Father-Centred Family (Rwala, Lamba); Factor Three: Tropical Rain Forest Culture (Trobriand, Siriono); Factor Four: Paternal Authority (Samoan, Navaho); Factor Five: Matrilineal Kin Groups (Trobriand, Semang); Factor Six: Status as Determined by Occupation (Thai, Lamba); Factor Seven: Aggressive Achievement Behaviour (Ashanti, Hano); Factor Eight: North American Tribal Culture (Cheyenne, Ashanti); Factor Nine: Child Affection and Indulgence (Papago, Thonga); Factor Ten: Sexual Restraint Cultures (Thonga, Ifugao); Factor Eleven:Post-partum sex taboo (Tiv, Tanala); Factor Twelve:Adolescent Peer Group Activity (Samoans,Jivaro). Within the limits of the study, these suggest key dimensions to describe a given culture, and it may be that future refinements of this work will permit the development of reliable and valid methods of ethnographic enquiry for the tapping of these major cultural dimensions.
Keywords: Robert B. Textor; "A cross-cultural summary" (Robert Textor); Cross-cultural studies; Cultural research